Cultivating Character Strength: Multicultural Perspectives in Islamic Education - Siskiyah Siskiyah; Nur Sofea Nazirah (Indonesian Journal of Education and Social Studies, 2022)
This study aims to describe efforts to strengthening the character of nationality through multicultural Islam education. As well as to describe the strengthening of the character of nationality through the multicultural Islamic education based on the application of the Sila on Pancasila in Mambaul Hikam Junior High School Situbondo. This study focuses on strengthening the character of nationality through Multicultural Islamic Education base of sila on pancasila. Data collection techniques used are interviews, participant observation (Participant Observation) and documentation techniques. The data that have been obtained from the informant are then analyzed. The results of this study indicate that the strengthening of the character of nationality through the education of Multicultural Islam is by implementing the character of nationality base of sila pancasila; First, dedicating the Islamic culture on the santri based on the first sila pancasila, second, instilling the Islamic-owned humanitarian character based on the second sila Pancasila, third, instilling the attitude of Gotong Royong according to the third Sila Pancasila, fourth, instilling the character of Islamic suspected leaders based on the fourth Pancasila, fifth, instilling social-character social-based and religious slabs. The application of Pancasila's sila to strengthen the character of nationality through Islamic education is also to keep harmony, creating a high tolerance, and keeps diversity differences so as not to be easily split among others.